Застосування заходів забезпечення кримінального провадження у підготовчому судовому провадженні: проблеми доказування - Завтур Віктор Андрійович; Завтур Виктор Андреевич; Zavtur V.A. (My University, 2016)
Статтю присвячено аналізу проблем та особливостей доказування при застосуванні заходів забезпечення кримінального провадження у підготовчому провадженні. Обґрунтовано необхідність оптимізації та вдосконалення відповідних норм КПК України

Статья посвячена анализу проблем и особенностей доказывания при применении мер обеспечения уголовного производства в подготовительном производстве. Обоснована не- обходимость оптимизации и усовершенствования соответствующих норм УПК Украины.

In this article certain aspects of the lodging of evidences, facts to proof and some connected issues of enforcing measures to ensure criminal proceedings at preparatory proceedings are exam- ined. It was defined that the enforcing measures to ensure criminal proceedings has another judicial essence in comparison with another matters which are examined at preparatory proceedings. It’s pointed out that the evidential activity in examination of appropriate applications has specific peculiarities. The necessity of lodging evidences by the parties of criminal proceedings to support their attitude regarding the certain measure of restraint is outlined. The peculiarities of the facts to proof in applying measures to ensure criminal proceedings at preparatory proceedings were found out. It was emphasized that court is able to take into account some additional retrospective actual circumstances making a decision to enforce certain measure of restraint such as: the behavior of accused person at pre-trial proceedings, information about unlawful influence on victims, the facts related to the cooperation in detection of criminal offence, the compen - sation of damage caused to the victim, the infringement of obligations connected with the previous measure of restraint. The points of view of the scientists who emphasize the necessity of automatic abolition of the current measures to ensure at the preparatory proceedings are supported. It was concluded about the necessity of creation the separate order of applying measures to en- sure criminal proceedings at preparatory judicial proceedings. Author’s edition of art. 315–1 of CPC of Ukraine was proposed.
Завтур В. А. Застосування заходів забезпечення кримінального провадження у підготовчому судовому провадженні: проблеми доказування / В. А. Завтур // Вісник кримінального судочинства. – 2016. – № 1. – С. 105-111.
Keywords: заходи забезпечення кримінального провадження; запобіжні заходи; тримання під вартою; підготовче провадження; підготовче судове засідання; доказування; меры обеспечения уголовного производства; меры пресечения; содержание под стражей; подготовительное производство; подготовительное судебное заседание; доказывание; measures to ensure criminal proceedings; measures of restraint; keeping in custody; preparatory proceedings; preparatory court session; proving